Reproductive risk factors and breast cancer: a case control study from rural India (Bangladesh Journal of Medical Science, 2015)
Background: Breast cancer is the most common type of cancer in women and is influenced by reproductive factors perceived by women worldwide.Aims: To identify the reproductive risk factors of breast cancer in newly diagnosed cases and to find out the strength of association of the risk factors with the breast cancer. Material and Methods: A hospital based case-control study was conducted in Satara district, India during year 2009 to 2011 among newly diagnosed cases of breast cancer and matched controls. A total of 434 participants including 217 cases and 217 controls were enrolled by purposive sampling technique from selected hospitals of study area. The information was collected by employing pre-tested questionnaire by utilizing interview method. Statistical Analysis used: Descriptive statistics, Odds ratio and Chi-square test was used to find out strength of association and statistical significant difference. Results: Highest proportion [31.80%] breast cancer cases was in age group 40-49 years with lowest age of 25 years at diagnosis of the disease. A very high proportion of both cases [88.02%] and controls [67.28%] were Hindu by religion and were from rural residence. Maximum proportion of breast cancer cases were housewives [63.59%], literate [71.42%] and from upper economic class [56.68%]. The proportions of cases were higher as compared to the controls with respect to risk factors like unmarried status, nulliparity, history of abortion, post menopausal status, absence of breast feeding and the history of exposure to hormonal contraceptives. The risk of getting breast cancer as indicated by Odds ratio was 8 times higher in unmarried women, 2.8 times in nulliparous women, 2.4 times with post menopausal status, 10.4 times with absence of breast feeding, 1.5 times with exposure to hormonal contraceptives and 4.5 times with history of ovarian disease respectively. Conclusion: The reproductive risk factors such as unmarried status of women, nulliparity, menopause, absence of breast feeding, history of ovarian disease and use of contraceptives were strongly associated with breast cancer.Bangladesh Journal of Medical Science Vol.14(3) 2015 p.258-264